2021
DOI: 10.1016/j.redox.2021.101863
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA Meg3 deficiency impairs glucose homeostasis and insulin signaling by inducing cellular senescence of hepatic endothelium in obesity

Abstract: Obesity-induced insulin resistance is a risk factor for diabetes and cardiovascular disease. However, the mechanisms underlying endothelial senescence in obesity, and how it impacts obesity-induced insulin resistance remain incompletely understood. In this study, transcriptome analysis revealed that the long non-coding RNA (lncRNA) Maternally expressed gene 3 (Meg3) is one of the top differentially expressed lncRNAs in the vascular endothelium in diet-induced obese mice. Meg3 knockdown induces cellular senesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 101 publications
(84 reference statements)
2
33
0
Order By: Relevance
“…Moreover, we found that Meg3 deficiency promoted cellular senescence of the hepatic endothelium with no or minimal effects on cellular senescence of other cell types in the liver in diet-induced obese mice ( Cheng et al, 2021 ). Importantly, Meg3 knockdown impaired systemic glucose homeostasis and insulin signaling in the liver, which can be restored by attenuating the cellular senescence of hepatic endothelium, indicating that cellular senescence of the vascular endothelium impairs glucose homeostasis and insulin signaling in obesity ( Cheng et al, 2021 ). How Meg3 limits cellular senescence of ECs is unclear.…”
Section: Long Noncoding Rnas In Cellular Senescence Of Vascular Endotheliummentioning
confidence: 92%
See 4 more Smart Citations
“…Moreover, we found that Meg3 deficiency promoted cellular senescence of the hepatic endothelium with no or minimal effects on cellular senescence of other cell types in the liver in diet-induced obese mice ( Cheng et al, 2021 ). Importantly, Meg3 knockdown impaired systemic glucose homeostasis and insulin signaling in the liver, which can be restored by attenuating the cellular senescence of hepatic endothelium, indicating that cellular senescence of the vascular endothelium impairs glucose homeostasis and insulin signaling in obesity ( Cheng et al, 2021 ). How Meg3 limits cellular senescence of ECs is unclear.…”
Section: Long Noncoding Rnas In Cellular Senescence Of Vascular Endotheliummentioning
confidence: 92%
“…Meg3 knockdown causes cellular senescence of HUVECs characterized by accelerated telomere length shortening, an increase in the levels of superoxide, an increase in SA-β-gal activity, impaired autophagy, and mitochondrial dysfunction (Lan et al, 2019;Cheng et al, 2021). Moreover, we found that Meg3 deficiency promoted cellular senescence of the hepatic endothelium with no or minimal effects on cellular senescence of other cell types in the liver in diet-induced obese mice (Cheng et al, 2021). Importantly, Meg3 knockdown impaired systemic glucose homeostasis and insulin signaling in the liver, which can be restored by attenuating the cellular senescence of hepatic endothelium, indicating that cellular senescence of the vascular endothelium impairs glucose homeostasis and insulin signaling in obesity FIGURE 4 | The role of maternally expressed gene 3 (Meg3) in regulating endothelial cellular senescence.…”
Section: Maternally Expressed Genementioning
confidence: 99%
See 3 more Smart Citations